EXAMINING TAX RECEIVABLES MANAGEMENT PRACTICES IN THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE - Ambarwati, Ria Dewi; Andriana, Nina; Aprilia, Rachma; Hartopo, Wing; Iswandy, Iis (Unit Penerbitan Politeknik Keuangan Negara STAN, 2025)
From the results of the BPK audit of the Ministry of Finance's Financial Report for 2021 to 2023, there are still repeated findings related to the administration of tax receivables at the Directorate General of Customs and Excise. This study examined the practice of tax receivables administration at DJBC. This study is a qualitative study with a descriptive approach. The type of data used is primary data through questionnaires and FGD implementation, and secondary data. The analysis tool in this study uses a rating scale analysis to measure, compare, and evaluate the related tax receivables administration practices. Based on the results and discussion, of all stages of tax receivables administration at the Directorate General of Customs and Excise assessed by respondents, the one that received the highest rating was at the receivables reporting stage, with a rating of 94.83% of the criteria scale or 4.74 (likert scale 5). Meanwhile, the lowest rating of tax receivables administration at the Directorate General of Customs and Excise is at the stage of receivables transfer, with a rating of 88.92% of the criteria scale or 4.45 (likert scale 5). DJBC can use the practical implications of this finding in implementing priority strategies in solving problems in DJBC tax receivables administration.